Virtual planning on contralateral hemipelvis for posteriorly fixed acetabular fractures. - Agarwal, Gaurang; Mishra, Abhishek; Verma, Tarun; Kumar, Raj; Meena, Abhay; Maini, Lalit (European Journal of Trauma & Emergency Surgery, 2022)
Background: Open reduction and internal fixation is a standard treatment for displaced acetabular fractures using 3.5 mm reconstruction plates contoured intra-operatively. This process is difficult and time consuming hence resulting in increased surgical morbidity. Virtual surgical planning is now being commonly used worldwide to aid in management of such complex problems. Patient-specific reconstruction plate pre contoured using virtual surgical planning on contralateral intact hemipelvis will be helpful in achieving better surgical outcomes. Also, it has an added advantage of considerably reducing the time and effort spent in virtual pre-operative planning process. Methodology: This study was performed in 30 patients with acetabulum fracture who were fixed posteriorly via Kocher-Langenbeck approach. Virtual planning was done on contralateral hemipelvis to prepare patient-specific pre-contoured plates and mirrored to the fractured side. The time required for virtual planning on fractured and normal side was recorded and compared. The efficiency of plates so prepared were accessed in terms of outcome variables like duration of surgery, blood loss, reduction obtained on X-ray as well as CT Scan. Result: Time required for virtual planning was more on fractured side and lesser when it was done using normal hemipelvis with mean values of 81.83 (sd = 28.02) min and 15.67 (sd = 6.12) min, respectively. Values of blood loss, duration of surgery and reduction as accessed on X-ray and CT scan were comparable or even better than compared to other studies. Conclusion: Contralateral normal pelvis can be used for virtual preoperative planning making the whole process easier and less time consuming.